Response of gyroid lattice structures to impact loads. (June 2022) - Ramos, Henrique; Santiago, Rafael; Soe, Shwe; Theobald, Peter; Alves, Marcílio
Highlights: Static and dynamic mechanical characterization of additive manufacturing AlSi10Mg alloy. Dynamic response evaluation of gyroid structures with experimental and numerical validation. Topological analysis of the gyroid structures under compressive impact conditions. Abstract: This paper reports on a comprehensive investigation of gyroid lattice structures subject to impact loading. AlSi10Mg samples were manufactured using selective laser melting (SLM) and mechanically characterized using Digital Image Correlation (DIC). Universal testing machines, drop weight rig, and a split pressure Hopkinson bar were used to mechanically characterize the aluminium alloy at strain rates ranging from, ε ˙ = 10 − 3 s − 1 up to 5500 s − 1 . Gyroid samples were tested in a drop-weight rig at different impact conditions, where tests results were validated by a FE analysis. These tests, measurements, and analysis enabled the development of a modified gyroid isosurface equation, providing an opportunity to investigate their impact response, where the gyroid wall thickness, unit cell size, and modified isosurface curvature were studied at low-velocity impact conditions. The results indicate that changes in gyroid isosurface topology substantially affect its impact performance.